Word order in wh-questions in a North Norwegian dialect: some evidence from an acquisition study - Westergaard, Marit (Nordic Journal of Linguistics, 2003)
While standard Norwegian is a V2 language, some Norwegian dialects exhibit V3 in certain types of wh-questions. In some previous work on the Tromsø dialect, V3 has been considered the ‘true’ dialect and speakers' acceptance of V2 simply a result of the influence from the standard language. Based on child and adult data from a study of the acquisition of word order in the Tromsø dialect, I will argue that both V2 and V3 orders are part of the dialect – used by adult speakers and acquired (more or less) simultaneously by children. It will further be argued that the choice between the two depends on the information structure of the sentence, more specifically, on the interpretation of the subject as given or new information.